2021
DOI: 10.3390/nu13041181
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Supplementation Improves Blood Pressure and Reduces Aortic Root Lesions in an Atherosclerosis-Prone Genetic Mouse Model

Abstract: Epidemiological studies have shown that carrot consumption may be associated with a lower risk of developing several metabolic dysfunctions. Our group previously determined that the Bolero (Bo) carrot variety exhibited vascular and hepatic tropism using cellular models of cardiometabolic diseases. The present study evaluated the potential metabolic and cardiovascular protective effect of Bo, grown under two conditions (standard and biotic stress conditions (BoBS)), in apolipoprotein E-knockout (ApoE−/−) mice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…This lipid-lowering effect could potentially prevent cardiovascular disease in diabetes, which is also supported by the decreased glucose levels in the treated groups, as discussed in Table 6. The previous findings agreed with Soleti et al [53], where a high-fat diet with carrot supplement showed antihyperglycemic and lipid-lowering activities due to its effect on improving pancreatic β-cells function. It has been established that various metabolic and regulatory abnormalities that occur during diabetes lead to hyperlipidemic conditions in people with diabetes, while increased TC, LDL-C, and TG levels in the blood cause diabetic dyslipidemia [71].…”
Section: Effect Of Supplemented Cupcakes On the Body Weight Gain And ...supporting
confidence: 91%
See 1 more Smart Citation
“…This lipid-lowering effect could potentially prevent cardiovascular disease in diabetes, which is also supported by the decreased glucose levels in the treated groups, as discussed in Table 6. The previous findings agreed with Soleti et al [53], where a high-fat diet with carrot supplement showed antihyperglycemic and lipid-lowering activities due to its effect on improving pancreatic β-cells function. It has been established that various metabolic and regulatory abnormalities that occur during diabetes lead to hyperlipidemic conditions in people with diabetes, while increased TC, LDL-C, and TG levels in the blood cause diabetic dyslipidemia [71].…”
Section: Effect Of Supplemented Cupcakes On the Body Weight Gain And ...supporting
confidence: 91%
“…Additionally, the diabetic groups that consumed different types of fibers had less food intake daily than the diabetic control group, indicating that dietary fiber intake may help reduce the symptoms of polyphagia in T2DM mice [52]. Along the same line, carrot supplementation induced a time-dependent body weight gain-fed high-fat diet in different groups [53]. To our knowledge, nothing was reported in the literature concerning the effect of dried carrot leaves on nutritional or biochemical parameters.…”
Section: Effect Of Supplemented Cupcakes On the Body Weight Gain And ...mentioning
confidence: 90%
“…Moreover, total plasma and serum carotenoid levels <1,000 nmol/L are associated with higher risk of chronic diseases (15). Accumulating evidence supports the protective effects of carotenoids against cardiovascular diseases, including hypertension, a crucial risk factor of CVD (16)(17)(18). Recently, the total carotenoid level was shown to be significantly associated with CVD markers, including SBP, pulse wave velocity, Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), blood insulin, triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) (9).…”
Section: Introductionmentioning
confidence: 99%